O ANTROPÓLOGO E A AÇÃO INDIGENISTA NO MARANHÃO - NUNES, Daniela de Fátima Ferraro (2007)
This work makes one analyzes concerning the insertion of the anthropologist in view of the current context of indigenistas politics that had been reformulated after-Constitution 1988 and are endorsed in the principle of the respect to the diversity of the aboriginal peoples. This is the moment of reconfiguration of the indigenista field, when it gains new actors, as the technician managing of governmental bodies that start to execute indigenistas politics, and it has extended the participation of the anthropologist.